2021
DOI: 10.1186/s13054-021-03725-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum renin and major adverse kidney events in critically ill patients: a multicenter prospective study

Abstract: Background Preliminary studies have suggested that the renin-angiotensin system is activated in critical illness and associated with mortality and kidney outcomes. We sought to assess in a larger, multicenter study the relationship between serum renin and Major Adverse Kidney Events (MAKE) in intensive care unit (ICU) patients. Methods Prospective, multicenter study at two institutions of patients with and without acute kidney injury (AKI). Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…Among others, Gleeson et al observed a significant association between direct renin measurement and mortality in a prospective observational study of critically ill adults [7]. Consistently, Flannery et al demonstrated that serum renin measured early after ICU admission was significantly and independently associated with mortality and major adverse kidney events, including kidney replacement therapy or reduced estimated glomerular filtration rate [8]. The prognostic value of renin and the importance of renin trajectory were recently confirmed in patients undergoing cardiac surgery [9].…”
Section: What We Know From Studies In Adult Patientsmentioning
confidence: 86%
See 1 more Smart Citation
“…Among others, Gleeson et al observed a significant association between direct renin measurement and mortality in a prospective observational study of critically ill adults [7]. Consistently, Flannery et al demonstrated that serum renin measured early after ICU admission was significantly and independently associated with mortality and major adverse kidney events, including kidney replacement therapy or reduced estimated glomerular filtration rate [8]. The prognostic value of renin and the importance of renin trajectory were recently confirmed in patients undergoing cardiac surgery [9].…”
Section: What We Know From Studies In Adult Patientsmentioning
confidence: 86%
“…The assay used by Stanski et al measured not only renin but also its precursor prorenin, whose plasma concentration in healthy subjects is significantly higher than that of its active form. Although renin production in stressful states exceeds prorenin release by 50-100-fold and prorenin is more stimulated by longer stimuli than by acute events, new low cross-reactivity assays for prorenin will be required in future trials, such as in some recent studies in adult patients [8]. Some concerns have been raised in the past about possible factors influencing renin levels in critically ill patients, but recent studies have clearly demonstrated that renin levels are not impacted by diurnal variation, medications, or continuous kidney replacement therapy (CKRT) [7].…”
Section: Measurement Techniquementioning
confidence: 99%
“…Limitations: The study is limited by the fact that serum renin was used as a surrogate for intrarenal RAS. Both plasma and serum renin have been analysed in other studies as measures of renal RAS [ 22 , 34 , 46 , 47 ], although it remains a proxy for actual intrarenal renin production. Although there are many advantages of investigating a pediatric population and providing new insights (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a multicenter, prospective study of critically ill patients admitted to the ICU at two large academic medical centers: the University of Texas Southwestern (UTSW) and the University of Kentucky (UKY) [ 23 , 24 ]. Inclusion criteria consisted of adult ICU patients (≥ 18 years old) with a known baseline eGFR ≥ 60 ml/min/1.73 m 2 .…”
Section: Methodsmentioning
confidence: 99%